"Wala kang utang na loob!" Adult Filipino children's experiences with regard to parental expectations - Alcantara, Nicole Anne G. (Animo Repository, 2022)
In a culture wherein the nuclear family is of utmost importance, the different perspectives that contribute to a deeper understanding of a Filipino family is observed. Due to this variation, the true meaning and essence of family has been redefined where an emphasis on what makes it whole and connected is placed. This study dissects the Adult Filipino Children’s perception on parental expectations and how Utang na Loob plays a role in the said expectations, while factoring in gender and birth order. The researchers recruited 11 participants through purposive sampling, and interviewed 3 of each gender (male, female, and LGBTQ+) considering various birth orders. Multiple superordinate themes were drawn from the data analysis. From these, the participants' responses were further grouped into subordinate themes that would be then categorized into subordinate themes. Subsequent to data analysis, as per participant’s responses, expectations vary from different participants and also depend on certain factors such as parentchild relationship and the type of expectations that were heavily imposed on the AFC. Concurrently, it was discovered that expectations that are deemed Educational, Occupational, Financial or Elderly Care could overlap with one another. In terms of the concept of Utang na Loob, analysis revealed that the concept is in fact complex due to the presence of other factors such as the foundation of the parent-child relationship. Individualistic family setting experiences are becoming more apparent, and Filipino culture is suspected to transition into a more globalized or Western thinking without discounting Filipino values.